JUSTIFICATION OF PARAMETERS OF FERMENTATION OF MILK MIXTURES FOR LOW LACTOSE YOGURTS - SERENKO, ANTON; YUDINA, TETIANA (Herald of Khmelnytskyi National University. Technical sciences, 2023)
Today, the expediency of creating new formulations and technologies of dairy products with reduced lactose content is due primarily to their high demand and narrow range of domestic production. A promising direction in the development of new technologies for dairy products with regulated carbohydrate composition is the rational use of the nutritional potential of secondary dairy raw materials. It applies particularly to low-lactose yogurts. The aim of the work is to substantiate the fermentation parameters of milk mixtures with an increased content of dry substances and hydrolyzed lactose for the production of low-lactose yogurts based on crumb. The subject of the research is milk mixtures based on buttermilk normalized by the content of dry substances and hydrolyzed lactose; directly applied leavening agent for yogurt production. Lactose content was determined by the chromatographic method on an LC-20 liquid chromatograph (Shimadzu) with a refractometric detector. Physic-chemical indicators of the samples were determined according to generally accepted standardized research methods. The process of formation of sour-milk clots in milk mixtures with an increased content of dry substances and hydrolyzed lactose was studied. The parameters of the process of fermentation of milk mixtures for the production of low-lactose fermented milk drinks have been determined. For the fermentation of milk mixtures, we used YC-X11 direct starter (Chr. Hansen, Denmark), which includes cultures of lactic acid bacteria Streptococcus thermophilus and Lactobacillus delbrueckii ssp. Bulgaricus. It was established that the lactic-coagulant activity of the leavening preparation and the rate of formation of a sour-milk clot was 15-20% higher in samples with hydrolyzed lactose. The rational parameters of fermentation of milk mixtures based on crumbs with an increased content of dry substances and hydrolyzed lactose are substantiated: the dose of adding YC-X11 sourdough starter is 2.3...2.6 mg, the fermentation temperature is 40±2oC, the duration of the process is 210...240 minutes.